Weightbearing CT in normal hindfoot alignment — Presence of a constitutional valgus?. Issue 3 (June 2018) - Burssens, A.; Van Herzele, E.; Leenders, T.; Clockaerts, S.; Buedts, K.; Vandeputte, G.; Victor, J.
Highlights: The normal hindfoot angle is estimated between 2 and 6° of valgus, but these results are solely based on clinical findings and plain radiographs. Weightbear CT overcomes these limitations by providing accurate measurements of bone position together with a natural stance of the patient. Determing the hindfoot alignment using the inferior point of the calcaneus in patients without hindfoot pathology showed a more neutral hindfoot angle. This inferior point showed the presence of an increased bone density, indicating a higher load exposure and biomechanical relevance. These findings can be used to determine the hindfoot position during fusion or in quantifying the correction of a malalignment. Abstract: Background: The normal hindfoot angle is estimated between 2° and 6° of valgus in the general population. These results are solely based on clinical findings and plain radiographs. The purpose of this study is to assess the hindfoot alignment using weightbear CT. Methods: Forty-eight patients, mean age of 39.6 ± 13.2 years, with clinical and radiological absence of hindfoot pathology were included. A weightbear CT was obtained and allowed to measure the anatomical tibia axis (TAx) and the hindfoot alignment (HA). The HA was firstly determined using the inferior point of the calcaneus (HAIC ). A density measurement of this area was subsequently performed to analyze if this point concurred with an increased ossification, indicating a higher load exposure. Secondly the HA was determined by dividing the calcaneus in the long axial view (HALA) and compared to the (HAIC ) to point out any possible differences attributed to the measurement method. Reliability was assessed using an intra class correlation coefficient (ICC). Results: The mean HAIC equaled 0.79° of valgus ± 3.2 (ICCHA IC = 0.73) with a mean TAx of 2.7° varus ± 2.1 (ICCTA = 0.76). The HALA equaled 9.1° of valgus ± 4.8 (ICCHA LA = 0.71) and differed significantly by a P < 0.001 from the HAIC, which showed a more neutral alignment. Correlation between both was shown to be good by a Spearman's correlation coefficient of 0.74. The mean density of the inferior calcaneal area equaled 271.3 ± 84.1 and was significantly higher than the regional calcaneal area ( P < 0.001). Conclusions: These results show a more neutral alignment of the hindfoot in this group of non-symptomatic feet as opposed to the generally accepted constitutional valgus. This could have repercussion on hindfoot position during fusion or in quantifying the correction of a malalignment. The inferior calcaneus point in this can be used during pre-operative planning of a hindfoot correction as an anatomical landmark due to its shown influence on load transfer.